Flexible surface acoustic wave technology for enhancing transdermal drug delivery - Jikai Zhang; Duygu Bahar; Hui Ling Ong; Peter Arnold; Meng Zhang; Yunhong Jiang; Ran Tao; Luke Haworth; Xin Yang; Chelsea Brain; Mohammad Rahmati; Hamdi Torun; et al. (Drug Delivery and Translational Research, 2025)
Transdermal drug delivery provides therapeutic benefits over enteric or injection delivery because its transdermal routes provide more consistent concentrations of drug and avoid issues of drugs affecting kidneys and liver functions. Many technologies have been evaluated to enhance drug delivery through the relatively impervious epidermal layer of the skin. However, precise delivery of large hydrophilic molecules is still a great challenge even though microneedles or other energized (such as electrical, thermal, or ultrasonic) patches have been used, which are often difficult to be integrated into small wearable devices. This study developed a flexible surface acoustic wave (SAW) patch platform to facilitate transdermal delivery of macromolecules with fluorescein isothiocyanates up to 2000 kDa. Two surrogates of human skin were used to evaluate SAW based energized devices, i.e., delivering dextran through agarose gels and across stratum corneum of pig skin into the epidermis. Results showed that the 2000 kDa fluorescent molecules have been delivered up to 1.1 mm in agarose gel, and the fluorescent molecules from 4 to 2000 kDa have been delivered up to 100 µm and 25 µm in porcine skin tissue, respectively. Mechanical agitation, localised streaming, and acousto-thermal effect generated on the skin surface were identified as the main mechanisms for promoting drug transdermal transportation, although micro/nanoscale acoustic cavitation induced by SAWs could also have its contribution. SAW enhanced transdermal drug delivery is dependent on the combined effects of wave frequency and intensity, duration of applied acoustic waves, temperature, and drug molecules molecular weights. Graphical Abstract Graphical Abstract: Flexible surface acoustic wave technology for enhancing transdermal drug delivery